2022
DOI: 10.1186/s13005-022-00337-y
|View full text |Cite
|
Sign up to set email alerts
|

Onlays/partial crowns versus full crowns in restoring posterior teeth: a systematic review and meta-analysis

Abstract: Background Tooth-colored onlays and partial crowns for posterior teeth have been used increasingly in clinics. However, whether onlays/partial crowns could perform as well as full crowns in the posterior region was still not evaluated thoroughly. Methods A literature search was conducted without language restrictions in Pubmed, Embase, Cochrane Central Register of Controlled Trial and Web of science until September 2021. RCTs, prospective and retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…A systematic review of clinical studies, which compared onlays and full‐coverage crowns confirmed high survival rates of 93.5% and 95.38% with no statistical difference between the groups after five years 40 . Another recently published review with meta‐analysis, found equally survival and success rates for both treatment options of onlays/partial crowns and complete crowns after one and 3 years of service 41 . Clinical long‐term studies of heat pressed and CAD/CAM‐fabricated monolithic LDS crowns, occlusal veneers with a shoulder preparation and partial‐coverage restorations reported also high survival rates of 80.1%–96.75% after 15–16.9 years, 100% after 11–13 years and 95.27% after 16.9 years of function 29,31,33,48 …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A systematic review of clinical studies, which compared onlays and full‐coverage crowns confirmed high survival rates of 93.5% and 95.38% with no statistical difference between the groups after five years 40 . Another recently published review with meta‐analysis, found equally survival and success rates for both treatment options of onlays/partial crowns and complete crowns after one and 3 years of service 41 . Clinical long‐term studies of heat pressed and CAD/CAM‐fabricated monolithic LDS crowns, occlusal veneers with a shoulder preparation and partial‐coverage restorations reported also high survival rates of 80.1%–96.75% after 15–16.9 years, 100% after 11–13 years and 95.27% after 16.9 years of function 29,31,33,48 …”
Section: Discussionmentioning
confidence: 96%
“…40 Another recently published review with meta-analysis, found equally survival and success rates for both treatment options of onlays/partial crowns and complete crowns after one and 3 years of service. 41 Clinical long-term studies of heat pressed and CAD/CAM-fabricated monolithic LDS crowns, occlusal veneers with a shoulder preparation and partial-coverage restorations reported also high survival rates of 80.1%-96.75% after 15-16.9 years, 100% after 11-13 years and 95.27% after 16.9 years of function. 29,31,33,48 The results of the present in-vitro study showed that PCRs revealed higher failure load values compared to complete coverage crowns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations